Extracellular vesicles in kidneys and their clinical potential in renal diseases - Lee, Sul A (Kidney Res Clin Pract, 2021)
Extracellular vesicles (EVs), such as exosomes and microvesicles, are cell-derived lipid bilayer membrane particles, which deliver information from host cells to recipient cells. EVs are involved in various biological processes including the modulation of the immune response, cell-to-cell communications, thrombosis, and tissue regeneration. Different types of kidney cells are known to release EVs under physiologic as well as pathologic conditions, and recent studies have found that EVs have a pathophysiologic role in different renal diseases. Given the recent advancement in EV isolation and analysis techniques, many studies have shown the diagnostic and therapeutic potential of EVs in various renal diseases, such as acute kidney injury, polycystic kidney disease, chronic kidney disease, kidney transplantation, and renal cell carcinoma. This review updates recent clinical and experimental findings on the role of EVs in renal diseases and highlights the potential clinical applicability of EVs as novel diagnostics and therapeutics.